The friends and family test: a qualitative study of concerns that influence the willingness of English National Health Service staff to recommend their organisation - Dixon-Woods, Mary (SAGE Publications, 2014)
OBJECTIVES: The views of practitioners at the ‘sharp end’ of care provision are increasingly recognised as important indicators of quality of care. The National Health Service (NHS) Staff Survey in England has quantified employees' views on how far they would be happy with the standard of care provided by their organisation if a friend or family member needed treatment. We aimed to characterise the concerns that might affect the willingness of staff to recommend their own organisations. DESIGN: Qualitative study involving semi-structured interviews. Data analysis based on the constant comparative method. PARTICIPANTS: Members of clinical and managerial staff in four NHS organisations (n = 70), and senior stakeholders across the NHS including clinicians, managers and others with a strategic or senior-level perspective (n = 98). SETTING: One hundred and sixty-eight interviews were conducted: 70 in four case study organisations and 98 across the wider English NHS. MAIN OUTCOME MEASURES: Not applicable. RESULTS: Asking study participants the ‘if a friend…’ question offered insider views on the quality of care. Some staff had no concerns, but others, identified significant problems with consistency, reliability and behaviour of staff. Participants identified reasons for poor care that included inadequate organisational systems; structural problems of understaffing and under-resourcing; weaknesses in professional cultures and professional competence and failure to deal with problems such as unacceptable conduct. Participants emphasised that staff were not always able to deliver high-quality care because they worked in difficult conditions. CONCLUSIONS: Asking staff to give accounts of their willingness to recommend their organisation to family and friends elicits important insights into quality and safety of care. Such accounts might be able to provide warning signs that could signal organisational decline and avert healthcare scandals, but use outside a research context requires further evaluation.